THE THOUGHT OF KH IMAM ZARKASYI ON MULTICULTURAL EDUCATION AT MODERN ISLAMIC BOARDING SCHOOL GONTOR PONOROGO - Fisher Zulkarnain (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2015)
KH. Imam Zarkasyi is one of the founders of Islamic Boarding School “Darussalam” Gontor (PMDG) and at once became a national figure. Author describes multicultural education in the perspective KH Imam Zarkasyi, then take measurements on the practice of multicultural education in PMDG. This study suggests, since KH. Imam Zarkasyi PMDG founded in 1926 have established an atmosphere of multicultural education are covered by the system of formal curriculum and daily life activities. Under the existing system, Pondok Modern Gontor potential to develop multicultural education insightful and worthy of being an example of successful implementation of multicultural education in Indonesia. It can be seen from classroom practice, exchange dormitory, five principal of boarding, interaction between the consulate, and the synthesis of education applied in Pondok Modern Gontor for many years.